Efforts to Manage Plastic Waste Through Creative and Environmentally Friendly Activities for the Community at PKBM Hang Tuah Dua - Faiza Syahrani; Olivia Siringo-ringo; Riana Stefani Sinaga; Rika Fitri Ramadani (Yayasan Daarul Huda Kruengmane, 2026)
Plastic waste is one of the environmental problems caused by the high use of plastic and poor waste management. One effort to reduce plastic waste is through the use of ecobricks. This training activity was conducted at PKBM Hang Tuah Dua to improve community knowledge and skills in processing plastic waste into useful and environmentally friendly products. The methods used were presentations, demonstrations, direct practice, and mentoring. The results showed that participants were able to understand and practice the ecobrick-making process properly. In addition, the activity increased participants’ awareness of the importance of environmental cleanliness and plastic waste management. This training is expected to encourage the community to apply sustainable and creative waste management practices.